Transverse seismic response of diamond-shaped pylon in cable-stayed bridge: Experiment and analysis. (1st January 2022) - Zhang, Chao; Wen, Jianian; Han, Qiang; Du, Xiuli; Lai, Zhichao; Fu, Guanghui
Highlights: A reduced-scale specimen of the diamond-shaped pylon was tested under cyclic quasi-static load to investigate its seismic performance. The damage patterns and the hysteretic responses of the diamond-shaped pylon were evaluated. The developed FE model is able to replicate the performed experimental tests. The geometric configurations, loading protocols, and stiffness of crossbeam significantly affect the seismic performance of diamond-shaped pylon. Abstract: The diamond-shaped pylons have been widely used in engineering practice, due to their cost effectiveness and appealing aesthetics, particularly for the cable-stayed bridges with large clearance. However, the diamond-shaped pylons have both inward and outward inclinations, which may result in complicated seismic behavior when subjected to earthquake excitations. To this end, the seismic performance of a typical diamond-shaped pylon in the transverse direction is investigated in this paper. A reduced-scale specimen of the diamond-shaped pylon was tested under cyclic quasi-static load to evaluate the damage patterns and the hysteretic responses. The numerical models of the diamond-shaped pylon were developed and then verified against the experimental results. The effects of the geometric configurations, loading protocols, and stiffness of crossbeam on the seismic performance of the diamond-shaped pylon are assessed based on the numerical results of parametric studies. The test results indicate that the plastic hinges were formed at the diamond-shaped pylon legs near the middle intersections. The following parametric analyses imply that the failure modes and damage regions would be changed with the pylon shapes, stiffness of lower and middle crossbeams, and loading protocols.